USING PEER EDITING TO IMPROVE STUDENTS’ WRITING SKILL - Syakirman, Ahmad (JURNAL LITERARY CRITICISM, 2016)
The objectives of the study are describing the Implementation of peer-editing technique to improve students? writing skill and describing whether peer-editing technique can improve students? writing skill or not. This Study was undertaken in Vocational School of SMA Negeri 4 Kota Bengkulu. The subjecst of the research are the second year students of X IBB2 of SMA Negeri 4 Kota Bengkulu., who consit of 30 students. The researcher collected the data of the research observation, interview, document, and test (pre-test, post-test1,post-test2).In this research the researcher applied classroom action research which requires four steps, namely planning, implementing, observing, and reflecting. The result of this study shows that teaching writing usingpeer-editing can improve the students? writing ability. It is proved by the improvement of the students? mean score.The mean score of pre-test is 49,6%, while the mean score of post-test is 79,20%. In addition the students also fell intersted, motivated, and easy in writing class. Key Words: Peer Editing, Writing Skill